Cordycepin Decreases Ischemia/Reperfusion Injury in Diabetic Hearts via Upregulating AMPK/Mfn2-dependent Mitochondrial Fusion - Yu, Houyou; Hong, Xin; Liu, Lihua; Wu, Yangpeng; Xie, Xuemei; Fang, Guoxiang; Zhi, Shaomin (Frontiers in Pharmacology, 2021)
Diabetes mellitus is considered to be a major risk factor for cardiovascular disease, the most common cause of death in diabetes. However, therapeutic strategies for myocardial protection in patients with diabetes are still limited. Cordycepin is a traditional Tibetan medicine with a long history of widespread use, and exerts a wide range of anti-tumor, anti-inflammatory, and anti-oxidative effects. In recent years, although the therapeutic potential of cordycepin has attracted the attention of researchers, it remains unknown whether cordycepin plays a protective role in myocardial ischemia/reperfusion (MI/R) injury in diabetic patients. Here, using a diabetic mouse model, we found that cordycepin protected diabetic hearts from MI/R injury by promoting mitochondrial fusion and Mfn2 expression. Our in vitro results showed that cordycepin enhanced Mfn2-medicated mitochondrial fusion, improved mitochondrial function, and reduced cardiomyocyte apoptosis in high-glucose/high-fat cultured simulated ischemia/reperfusion cardiomyocytes. Furthermore, we found that knockout of Mfn2 significantly blocked the cardioprotective effects of cordycepin in diabetic mice. Finally, an AMPK-dependent pathway was found to upregulate Mfn2 expression upon cordycepin treatment, indicating that cordycepin protected diabetic hearts via AMPK/Mfn2-dependent mitochondrial fusion. Collectively, our study firstly demonstrated that cordycepin could be a potential cardioprotective agent for MI/R injury, and we established a novel mechanism by which upregulated AMPK/Mfn2-dependent mitochondrial fusion contributes to the cardioprotective role of cordycepin.